A case report on fetal acrania - D., Rita; B., Sirisha (International Journal of Research in Medical Sciences, 2025)
Fetal acrania is a rare but lethal congenital malformation within the acrania-exencephaly-anencephaly spectrum, characterized by complete absence of the cranial vault, meninges, and overlying scalp. The reported incidence is 1.4-2 per 1000 births in India, making it one of the most common neural tube defects after cardiac anomalies. Early detection through ultrasonography is crucial for counselling, prevention of maternal complications, and guiding reproductive planning. A 21-year-old primigravida presented at 16 weeks of gestation for routine antenatal care. She was unbooked case. Diagnosis of acrania was established by ultrasound, and the patient was managed with medical termination of pregnancy following counselling. Early sonographic diagnosis is vital for appropriate counselling and decision-making. Pre-conceptional folic acid supplementation remains the most effective preventive measure against neural tube defects.